Study of the deformation of sponge application hemostatic materials - V. A. Lipatov; D. A. Severinov; M.D. Z. Naimzda; E. L. Puchkova (Исследования и практика в медицине)
Purpose of the study. To evaluate the dynamics of deformation of spongy application hemostatic materials in an in vitro experiment. Materials and methods. As materials of the study the following samples of hemostatic materials were used: Tachocomb (No. 1), Gelita-Spon Standard (No. 2), Reggicel Fibrillar (No. 3), samples of hemostatic sponges developed jointly with Lintex (St.Petersburg, Russia) on the basis of sodium-Carboxymethyl Cellulose (No. 3): Samples were placed on a glass substrate which was mounted on the rising REM cross-arm 0.2–1 to estimate 50% compression residual strain. A glass substrate rigidly attached to the indenter was mounted so that its lower surface would touch the upper surface of the sample. The crossarm was then lifted at 30 mm/min, compressing the sample until the force reached 50 N, after which the sample was allowed to stand under pressure for 10 seconds. After the load was removed, the sample was removed from the substrate and the compression thickness measured (immediately after compression, after 5, 10 and 30 minutes). Results. The values of the compression residual deformation on the thickness 50% (immediately after the load removal) of the samples of group No. 1 differ statistically significantly from the values of groups No. 2 and No. 3 on 5.92 and 3.51, respectively. The difference between groups No. 1 and No. 4 is 5.61. The ODP values 50% 5 minutes after the load of Group No. 1 samples was removed differ from Groups No. 2 and No. 3 on 5.93 and 3.85, respectively. The difference between groups No. 1 and No. 4 is 6.57. After 30 minutes after compression, the values of the residual deformation of the samples of group No. 1 differ from those of groups No. 2 and No. 3 on 6.9 and 4.3. The difference between groups No. 1 and No. 4 is 6.9. Also, the values of the residual deformation of the samples of group No. 2 exceed the values of the samples of group No. 3 by 1.6 times, and in comparison with group No. 4 is less by 0.03. There are fewer statistical differences with other groups in pilot groups 5–7. Conclusion. The highest values of the indicator "residual deformation at compression by thickness 50%" are noted in group No. 7 (samples based on Na-CMC unpressurized) — 32.34, which causes high mechanical properties of jaws made from this material.